Highly Sensitive and Long-Term Stable Hydrogen Sensor for Real-Time Tracing of Dissolved Hydrogen in Transformer-Insulating Oil - Kondalkar, Vijay V.; Hwan Lee, Mun; Lee, Keekeun (2019 20th International Conference on Solid-State Sensors, Actuators and Microsystems and Eurosensors XXXIII, TRANSDUCERS 2019 and EUROSENSORS XXXIII, 2019)
Dissolved hydrogen gas analysis (DHA) has an essential role in transformer status and prevent safety issues of the power grid. The state of art sensor suffers from the ambient temperature variation and Joule heating effects interference for the DHA. We fabricated a hydrogen sensor based the wheatstone bridge with two sensors in a single system and Al2O3 passivation layer. The developed system constitutes two sensors in the wheatstone bridge with the same resistances and Pd materials in sensing resistors to eliminate the temperature variation and Joule heating effects occurring during operation. To obtain a better response sensor design optimized with respect to initial sensor resistance. COMSOL simulation was performed to optimise the micro-heater design. In an oil environment, the sensor shows 0.34 mV/ppm sensitivity in wheatstone bridge circuitry. The fabricated sensor achieved a high response, good repeatability, and long-term stability in oil, making it a promising candidate to serve for monitoring the condition of power transformers.
Keywords: Dissolved gas analysis; Dissolved hydrogen; Fabricated sensors; Hydrogen sensor; Joule heating effect; Long term stability; Temperature variation; Wheatstone bridges; Hydrogen Sensor; Palladium; Passivation A2O3; Wheatstone bridge Dissolved gas analysis